-(3-2N)+7N=(N+3)3

Simple and best practice solution for -(3-2N)+7N=(N+3)3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3-2N)+7N=(N+3)3 equation:


Simplifying
-1(3 + -2N) + 7N = (N + 3) * 3
(3 * -1 + -2N * -1) + 7N = (N + 3) * 3
(-3 + 2N) + 7N = (N + 3) * 3

Combine like terms: 2N + 7N = 9N
-3 + 9N = (N + 3) * 3

Reorder the terms:
-3 + 9N = (3 + N) * 3

Reorder the terms for easier multiplication:
-3 + 9N = 3(3 + N)
-3 + 9N = (3 * 3 + N * 3)
-3 + 9N = (9 + 3N)

Solving
-3 + 9N = 9 + 3N

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-3N' to each side of the equation.
-3 + 9N + -3N = 9 + 3N + -3N

Combine like terms: 9N + -3N = 6N
-3 + 6N = 9 + 3N + -3N

Combine like terms: 3N + -3N = 0
-3 + 6N = 9 + 0
-3 + 6N = 9

Add '3' to each side of the equation.
-3 + 3 + 6N = 9 + 3

Combine like terms: -3 + 3 = 0
0 + 6N = 9 + 3
6N = 9 + 3

Combine like terms: 9 + 3 = 12
6N = 12

Divide each side by '6'.
N = 2

Simplifying
N = 2

See similar equations:

| -6(x-12)+2(x+2)=x-9 | | -6(6y+2)-(-5y-8)=2 | | 1.96=r^2+2r+1 | | -4+2n+16=n+7 | | 1x-2(x+10)=12 | | 7x-9=-4x+90 | | 3(x+5)=3x | | 12*n=12*6 | | -(3-2N)+7N=(N+3) | | 18a-22=-4(1-6a) | | N*1=2 | | 50-6x=-46 | | -5b+24=-8b(b-6)+6b | | 2.5g-14=5 | | 9y^2-72y-81=0 | | x^2+2x+1=11 | | 7+4x=24 | | x^2+40x+384=0 | | 4y+7=6y+14 | | 7+3X=-15 | | -(4x-3)=x+6 | | 4x^2+15x-2.5=0 | | -8*4-6= | | 4x-3=x+6 | | -2=-4x-6x | | 4(3r-2)=3(r+7) | | 7+3x=-22 | | 2-6-4= | | (8x-10)+(8x-10)=6x+6x | | a(-10)-8=-24 | | -3(2x-4)+4x=-34 | | w+(w+6)=334 |

Equations solver categories